Effect of the lasers used in periodontal therapy on the surfaces of restorative materials. Issue 3 (4th September 2015) - Hatipoğlu, Mükerrem; Barutcigil, Çağatay; Harorlı, Osman Tolga; Ulug, Bülent
Summary: The present study aimed to reveal potential damage of the lasers, which are used as an alternative to manual instruments in periodontal therapy, might cause to the surface of restorative materials. Four different restorative materials were used: a glass‐ionomer cement (GIC), a flowable composite (FC), a universal composite (UC) and an amalgam. Ten cylindrical samples (8 mm × 2 mm) were prepared for each restorative material. Two laser systems were used in subgingival curettage mode; an 940 nm diode laser (Epic Biolase, Irvine, CA) and an Er, Cr:YSGG laser (Waterlase iPlus, Biolase, Irvine, CA). After laser irradiation, roughness of the sample surfaces was measured using a profilometer. Additionally, atomic force microscopy (AFM) and scanning electron microscopy (SEM) analyses were performed to evaluate the morphology and surface deformations of the restorative materials and surfaces. The laser irradiation did not affect the surface roughness of any restorative materials relative to that of the control group (p > 0.05) except for the Er, Cr:YSGG treatment on GIC (p < 0.05). SEM and AFM images verified the results of the surface roughness tests. Within the limitations of the present study, it was demonstrated that Er, Cr:YSGG and diode lasers, aside from the Er;Cr:YSGG treatment on GIC, caused no harmful surface effects on adjacent restorative materials. SCANNING 38:227–233, 2016. © 2015 Wiley Periodicals, Inc.